The Effect of Foreign Direct Investment, Environmental Quality, and Inflation on Economic Growth from in Asian G20 Countries for the Period 2014–2024: English - Raudhah Shalsabillah; Madnasir Madnasir; Mia Selvina (Jurnal REP (Riset Ekonomi Pembangunan), 2026)
This study aimed to analyze the effect of Foreign Direct Investment (FDI), Environmental Performance Index (EPI), and inflation on economic growth in Asian G20 countries, namely China, Indonesia, Saudi Arabia, India, and Japan, during the period 2014–2024 from an Islamic economic perspective. The research used a quantitative approach with secondary data obtained from the World Bank and Yale University. The data were analyzed using panel data regression, including Common Effect Model (CEM), Fixed Effect Model (FEM), Random Effect Model (REM), and Generalized Method of Moments (GMM). The results showed that inflation had a significant and positive effect on economic growth, while FDI and EPI had no significant effect. These findings indicated that maintaining price stability played a more dominant role in stimulating economic growth compared to foreign investment and environmental performance during the research period.